The Influence Of Promotion Mix On Consymers Purchasing Interest For Mixue Ice Cream And Tea Bengkulu City - Intan Dwi Putri; Ida Ayu Made; Anzori Anzori (Penerbit Jurnal Indonesia, 2023)
The company tries to increase consumer attractiveness for the products it offers, so the company chooses the methods used, especially in the marketing sector, to maintain the quality and quantity achieved. One of the right strategies to increase sales is a promotional mix. The promotional mix plays an important role in increasing the company's sales volume. Because of this, it is important for companies to promote through advertising, personal selling, sales promotion and publicity. The aim of this research is to determine the extent of the influence of promotion mix on consumers' purchasing interest for Mixue Ice Cream and Tea in Bengkulu City. The type of research used is quantitative. The method used is a questionnaire. The sample from this research was 85 respondents. The results of the research show that the multiple linear regression obtained Y = 2,790 + 0.579 (X1) + -0.300 (X2) + 0.401 (X3) + 0.211 (X4) + 2,163, meaning that there is a positive or unidirectional relationship between advertising, personal selling, sales promotion and publicity on consumers' purchasing interest for Mixue Ice Cream and Tea in Bengkulu City. The results of the advertising test (X1) show a significance of 0.000 < 0.05, so the results of Ha is accepted and Ho is rejected, meaning that advertising has a positive and significant effect on consumers’ purchasing interest for Mixue Ice Cream and Tea in Bengkulu City. The results of the personal selling test (X2) show a significance of 0.005 < 0.05, meaning Ha is accepted and Ho is rejected. The results of sales promotion test (X3) show a significance of 0.005 > 0.05, meaning Ha is accepted and Ho is rejected. The results of the publicity test (X4) show that the significance value is 0.83 > 0.05, meaning that Ha is rejected and Ho is accepted.